2017
DOI: 10.1039/c7ra00604g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating 131I into a PAMAM (G5.0) dendrimer-conjugate: design of a theranostic nanosensor for medullary thyroid carcinoma

Abstract: We report the synthesis and purification of a targeting probe for Medullary Thyroid Carcinoma (MTC) by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The results indicated that in all three cases, the iodine species absorbed onto Au NRs were iodine atoms with little ionic character. 31 However, considering the different radiochemical stability (Figure 1d In comparison, the radioactivity in MCF-7 cells treated with [ 131 I(0)] Au NRs-PEG demonstrated a time-dependent increase from 6.18 ± 0.84% at 4 h, 13.08 ± 0.83% at 12 h to 32.1 ± 6.1% at 24 h, consistent with the cellular internalization behavior of Au NRs (Figure S6). It seemed that [ 131 I(0)] Au NRs-PEG could efficiently deliver 131 I into cells due to the strong interaction between iodine and Au NRs.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The results indicated that in all three cases, the iodine species absorbed onto Au NRs were iodine atoms with little ionic character. 31 However, considering the different radiochemical stability (Figure 1d In comparison, the radioactivity in MCF-7 cells treated with [ 131 I(0)] Au NRs-PEG demonstrated a time-dependent increase from 6.18 ± 0.84% at 4 h, 13.08 ± 0.83% at 12 h to 32.1 ± 6.1% at 24 h, consistent with the cellular internalization behavior of Au NRs (Figure S6). It seemed that [ 131 I(0)] Au NRs-PEG could efficiently deliver 131 I into cells due to the strong interaction between iodine and Au NRs.…”
Section: Resultssupporting
confidence: 62%
“…The EB for I (3d 5/2 ) was shifted from 618 to 618.94 eV for Au + NaI aqueous solution, 619.24 eV for Au + preoxidized NaI, and 619.20 eV for Au + I 2 . The results indicated that in all three cases, the iodine species absorbed onto Au NRs were iodine atoms with little ionic character . However, considering the different radiochemical stability (Figure d–f) and morphology change (Figure e–h) of I (0) and I(−1) on Au NRs, we assumed that although both I(0) and I(−1) bond with Au as neutral iodine, I(0) chemically reacted with Au NRs, resulting in a stronger binding …”
Section: Resultsmentioning
confidence: 90%
“…In another study, Bossmann and co‐workers incorporated vascular targeting peptide (VTP) and radioisotope 131 I into G5 PAMAM dendrimers for SPECT imaging of medullary thyroid carcinoma (MTC) . VTP (sequence: GPLPLR) was reported to have high binding affinities towards umbilical vein endothelial cells via membrane‐bound matrix metalloproteinase MMP14, which is expressed in both angiogenic endothelium and tumor cells.…”
Section: Radiolabeled Dendrimer‐based Nanodevices For Targeted Nucleamentioning
confidence: 99%
“…Magnetic nanoparticles can be synthesized by using ionic and non-ionic techniques [43]. There are numerous methods known to synthesize magnetic nanoparticles, such as mechanical milling [44], co-precipitation [45], nanoreactor/microemulsion techniques [45,46], sonochemical processing [45,46], sol-gel methods [47], flow injection [43], electrochemical production [48], supercritical fluid techniques [49,50], thermal decomposition [13][14][15][16]22,[51][52][53][54][55], hydrothermal routes [45], microwave techniques [56], spray pyrolysis [45], laser pyrolysis [45], flame spray pyrolysis [45], gas phase synthesis [45], arc discharge [57], oxidation [58,59], and microbial methods etc. [43,45,60].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Magnetic nanoparticles play a big role in cancer detection [7][8][9], drug delivery [2,3], as well as hyperthermia treatment [10][11][12]. During the last decade, bi-magnetic core/shell nanoparticles featuring an iron core and an iron oxide (Fe 3 O 4 ) shell have become widely used [13][14][15][16][17][18][19], due to their superior magnetic properties [20,21].…”
Section: Introductionmentioning
confidence: 99%